Tata Keruangan Aktivitas Masjid Raya Ruhama Kota Takengon - Rejeki, Siska; Deni, Deni; Saputra, Eri (Jurnal Etnik: Ekonomi-Teknik, 2023)
The existence of a mosque is important for spreading the teachings of Islam. In addition to the versatility of the mosque to the community, the mosque is also a sign of the social piety of the surrounding population. The mosque, which is always full during prayer activities, shows the high enthusiasm for Islam in the community. However, currently there are mosques that lack the placement of space functions that are not in accordance with their activities, thus raising the question of whether the existence of the spaces contained in the mosque has been used according to its actual function. The number of mismatches in the function of space in the mosque makes the mosque lose its image and character. The research aims as one of the methods of finding indicators of the existence of a mosque that is in accordance with the use value that has been regulated in the Al-Quran and Hadith, so that later it can be known the suitability of its conception, both in teaching and, architectural science, and its use. The research uses a descriptive qualitative method, focusing on problems in the field based on facts that occur by making observations and observations, which are useful as a way to obtain a description of the conditions in the field. The research uses Henry Lefebvre theory of concept space, the elements studied are spatial practices and representations of space. The results of the research on the many spaces of the Raya Ruhama mosque, functioned by the community according to the activities that should be. As for the differences and discrepancies, they are only a result of the research.